2019
DOI: 10.1016/j.euf.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Resection of Bladder Tumors: Next-generation Virtual Reality Training for Surgeons

Abstract: We investigated how students without endoscopic experience profit from simulation-based training. The safe environment and repeated simulations can improve the surgical training. It may be possible to enhance patient's safety and the training of surgeons in long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 16 publications
1
27
0
2
Order By: Relevance
“…mid-urethral tape insertion), which is to be expected. Overall, the improvement in technical ability demonstrated through intensive simulation training is consistent with the evidence in contemporary literature that both high- and low-fidelity surgical simulators are useful tools in the acquisition of core urological skills [ 15 , 19 21 ]. For further details on how an intensive surgical simulation course can improve competency progression, our previous reports on evaluating trainee progression during simulation training highlight the issue [ 24 ].…”
Section: Evaluation Of Outcomessupporting
confidence: 83%
See 1 more Smart Citation
“…mid-urethral tape insertion), which is to be expected. Overall, the improvement in technical ability demonstrated through intensive simulation training is consistent with the evidence in contemporary literature that both high- and low-fidelity surgical simulators are useful tools in the acquisition of core urological skills [ 15 , 19 21 ]. For further details on how an intensive surgical simulation course can improve competency progression, our previous reports on evaluating trainee progression during simulation training highlight the issue [ 24 ].…”
Section: Evaluation Of Outcomessupporting
confidence: 83%
“…This is particularly relevant in times when clinical opportunities are rarer, such as the current COVID-19 pandemic. The UK urology curriculum contains several procedures which are amenable to simulation, exemplified by simulators designed specifically for ureteroscopy, cystoscopy, transurethral resection of the bladder (TURBT) and transurethral resection of the prostate (TURP) [ 15 , 19 21 ]. The engagement of trainees in such simulated procedures has been shown to be beneficial to improving clinical and operative skills [ 9 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, ESRD will create a serious socioeconomic burden worldwide. Alarmingly, even with regular nephrology follow-up of these ESRD patients, more than 60% of newly diagnosed ESRD patients are unplanned when starting renal replacement therapy [ 10 ] and often require emergency initiation of dialysis [ 11 ], although emergency initiation of dialysis is the preferred mode of initiation, it is still a common problem worldwide. Although it is the preferred mode of initiation, urgent initiation of dialysis is still a common problem worldwide, accounting for 30–50% of patients starting dialysis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual cystoscopy using VR seems to be predestined for this purpose. A recent study of Neumann et al [ 35 ] showed that this training method can have multiple advantages: Short training methods can improve efficacy and safety of VR-TURBT. It can decrease the procedural time and it can reduce accidental bladder injury and blood loss [ 35 ].…”
Section: Training For Transurethral Resection Of Bladder Tumorsmentioning
confidence: 99%
“…A recent study of Neumann et al [ 35 ] showed that this training method can have multiple advantages: Short training methods can improve efficacy and safety of VR-TURBT. It can decrease the procedural time and it can reduce accidental bladder injury and blood loss [ 35 ]. Comparable to other box simulators enhanced with VR or AR methods this new training method could help to speed up the adoption of this new diagnostic and surgical practice.…”
Section: Training For Transurethral Resection Of Bladder Tumorsmentioning
confidence: 99%